2017
DOI: 10.1007/s00259-017-3711-7
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnostic performance of 68Ga-PSMA-11 (HBED-CC) PET/CT in patients with recurrent prostate cancer: evaluation in 1007 patients

Abstract: PurposeSince the clinical introduction of 68Ga-PSMA-11 PET/CT, this imaging method has rapidly spread and is now regarded as a significant step forward in the diagnosis of recurrent prostate cancer (PCa). The aim of this study was to analyse the influence of several variables with possible influence on PSMA ligand uptake in a large cohort.MethodsWe performed a retrospective analysis of 1007 consecutive patients who were scanned with 68Ga-PSMA-11 PET/CT (1 h after injection) from January 2014 to January 2017 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

41
318
10
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 443 publications
(399 citation statements)
references
References 57 publications
41
318
10
13
Order By: Relevance
“…In this patient, we observed an excellent correlation between intrim 68 Ga-PSMA-HBED-CC PET/CT scans and sPSA response. In agreement with our indings, a retrospective analysis involving 1007 recurrent prostate cancer patients demonstrated a strong association of tumour detection and radiotracer avidity with sPSA levels [8].…”
Section: The Introduction Of 68supporting
confidence: 74%
See 1 more Smart Citation
“…In this patient, we observed an excellent correlation between intrim 68 Ga-PSMA-HBED-CC PET/CT scans and sPSA response. In agreement with our indings, a retrospective analysis involving 1007 recurrent prostate cancer patients demonstrated a strong association of tumour detection and radiotracer avidity with sPSA levels [8].…”
Section: The Introduction Of 68supporting
confidence: 74%
“…Ga-PSMA-HBED-CC PET/CT imaging has remarkably improved the accuracy of restaging the disease in recurrent prostate cancer [8]. Currently, 68 Ga-PSMA-HBED-CC PET/CT is the most widely accepted agent in the imaging of recurrent prostate cancer.…”
Section: The Introduction Of 68mentioning
confidence: 99%
“…Positive findings exclusively detected by 18 F-fluorocholine PET/CT were rare (36). Three large retrospective studies (including 319, 248, and 1,007 patients, respectively) reported detection rates for 68 Ga-PSMA-11 PET/CT in BCR of 88%, almost 90%, and 79.5%, respectively (38)(39)(40). In patients after curative treatment with a very low PSA level of less than 0.5 ng/mL the reported detection rate of PSMA ligand PET/CT ranged from 50% to 58% in different studies (36,(38)(39)(40).…”
Section: Main Clinical Indications Of Psma Ligand Pet/ct and Currentmentioning
confidence: 99%
“…Three large retrospective studies (including 319, 248, and 1,007 patients, respectively) reported detection rates for 68 Ga-PSMA-11 PET/CT in BCR of 88%, almost 90%, and 79.5%, respectively (38)(39)(40). In patients after curative treatment with a very low PSA level of less than 0.5 ng/mL the reported detection rate of PSMA ligand PET/CT ranged from 50% to 58% in different studies (36,(38)(39)(40). A recent study including only patients after prior radiotherapy (median PSA of 5.8 ng/mL) presented detection rates of 33.3% for a PSA of less than 0.5 ng/mL, 71.4% for a PSA of 0.5 to less than 1 ng/mL, and 93.3% for a PSA of 1 to less than 2 ng/mL.…”
Section: Main Clinical Indications Of Psma Ligand Pet/ct and Currentmentioning
confidence: 99%
“…shown promise for the detection of primary and recurrent prostate cancer (3)(4)(5)(6)(7). Since the introduction of integrated PET/MRI scanners, these complementary data sets can be simultaneously acquired, thereby potentially improving the diagnostic accuracy in comparison to either modality alone (3,4,8,9).…”
Section: Introductionmentioning
confidence: 99%